The Evolving Innovation Space : Variety of Innovations, Actors, Activities and Diffusion Mechanisms - Kunttu, Leena; Kalliomäki, Helka; Kuusisto, Jari (De Gruyter, 2024)
New societal challenges are setting growing demands for innovation policy on both international and national levels. To address societal challenges and create sustainable change, in addition to achieving economic benefits, it is important to recognize that the innovation space is evolving and getting more complex. This chapter considers how the understanding of the innovation space has evolved from the 1990s to today by using the definition of innovation and its related concepts in four editions of the Oslo Manual (OM) published by the Organisation for Economic Co-operation and Development (OECD) between 1992 and 2018. The topic of evolving innovation space is studied in three dimensions: 1) variety of innovations; 2) innovation actors and activities; and 3) innovation diffusion and spillovers. The analysis of the OM shows that the policy understanding of innovation has evolved from technological and manufacturing innovations to cover almost all areas of society, including the central role of users and customers in innovation processes. In addition, innovation diffusion has shifted from being viewed as a purely commercial process to include non-commercial processes. As a result, the OM can also be viewed as a means for charting the evolution of the innovation space and understanding how innovation activities can be measured.
Keywords: fi=Aluetiede|en=Regional Studies|